The Probe Team [episode no. 276] - Lazaro, Cheche (Probe Productions, 1993)
The celebrities, i.e., Martin and Pops Fernandez, Ruffa Gutierres, Annabelle Madeca, Juan Flavier and Gary Valenciano tell their favorite Christmas carol while the Madrigal Singers sing their songs for them.